KINERJA DINAS PENDIDIKAN DALAM PELAKSANAAN WAJIB BELAJAR 9 TAHUN DI PEKANBARU - Harpemi Zahratul Hayaty; Zaili Rusli (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2014)
Background problem in this study is a nine -year compulsory education since 1994 has announced a target that lesson all children aged 7-15 years receive a basic education services. The main problem that often arises in the success of the implementation of the nine-year compulsory education is how to ensure that children who have graduated from elementary school to junior high continuing education, both regular SMP, SMP or through programs open B. Package of the children who experienced dropouts actually means to have enough free time that can be used for education if the means that can be used for education if the facilities and assistance available. This condition can not be separated from the role of the Department of Education to participate in Pekanbaru in facilitating the presence of children who drop - out or can not continue the school though only up to a basic level ( primary and junior ) , to provide education Packet A or other facility.Keywords: Performance, nine-year compulsory education